1974
DOI: 10.1080/713818903
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Theoretical Study of the Anomalies of a Sinusoidal Diffraction Grating

Abstract: Theoretical counterparts are presented for the experimental efficiency curves obtained by Hutley and Bird in the visible region for a holographic grating covered consecutively with films of silver, aluminium and gold. It is thus shown that the recently developed formulation of Maystre, which takes into account the finite conductivity of the grating surface, gives results in quantitative agreement with experiment . This not only validates the theory, but also demonstrates that the difficulties associated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The experiments of Hutley and Bird [115] [116] and Neviere et al . [117] have convincingly demonstrated that there are important differences in the way infinite conductivity and finite conductivity gratings scatter .…”
Section: Appendixmentioning
confidence: 99%
“…The experiments of Hutley and Bird [115] [116] and Neviere et al . [117] have convincingly demonstrated that there are important differences in the way infinite conductivity and finite conductivity gratings scatter .…”
Section: Appendixmentioning
confidence: 99%
“…Consequently, it can be shown that the corrugated metal structure is equivalent to a uniform structure with material properties, which can be approximated by the Drude metal with a plasma frequency that depends only on the shape and dimensions of the corrugations. This is the analog of surface plasmons in diffraction gratings and their inner relation to Wood's anomaly [18][19][20]. Pendry's work was almost immediately followed by the experimental demonstration of spoof plasmons at microwave frequencies * mfarhat@hbku.edu.qa [21] and several other studies focusing on various structures capable of supporting spoof plasmons [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 94%
“…The scattering coefficients A l associated with this structure are deduced from Eqs. (18)- (20) and σ scat is again computed using Eq. (11).…”
Section: Localized Spms Induced On Corrugated Thin Plate Cylindersmentioning
confidence: 99%
“…forTM (35 ) and multiplication of Y I with the characteristic matrix of the multilayer results in a real A and imaginary B value in Equation (21).…”
Section: Bound Modesmentioning
confidence: 99%